If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(4x + 12) = -9 Reorder the terms: x(12 + 4x) = -9 (12 * x + 4x * x) = -9 (12x + 4x2) = -9 Solving 12x + 4x2 = -9 Solving for variable 'x'. Reorder the terms: 9 + 12x + 4x2 = -9 + 9 Combine like terms: -9 + 9 = 0 9 + 12x + 4x2 = 0 Factor a trinomial. (3 + 2x)(3 + 2x) = 0Subproblem 1
Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5Solution
x = {-1.5, -1.5}
| 3a+5b=26 | | 3r+38= | | 4x-10=-(9x+18) | | 4x^2+36y^2-72y-108=0 | | 17-10x=5x+65 | | 2x(x+3)=9 | | y^3-4y^2=0 | | 3(-2-x)=18 | | 7/8*6/5 | | 9m+24= | | 1/2w+7=2w-2 | | 27x-4=9x+2 | | x(x)-5+2forx=6 | | 2-4r=-14 | | 64x^3-49x=0 | | 2n=2n-1 | | 3t+2+2t=-53 | | x(x)-5+12= | | 5x^3+3x^2=125x+75 | | 8/11-2x=-2x+6/11 | | 5x^3/4+2=42 | | 29-5g+3=-3g+6g | | y+2=10 | | 32x-1/5=4 | | 3x-1/5=20 | | .2n-.594=3.5n+9.0 | | -.389y-.974=6.789y | | -3(2x-3)+15=9 | | 5(2x-6)=3(x+4) | | 15-(3m+7)=5+4m-18 | | 2x^2-10=20 | | 8y-6=7y+3 |